Frontispiece: Alkene–Tetrazine Ligation for Imaging Cellular DNA. Issue 35 (25th August 2014) - Rieder, Ulrike; Luedtke, Nathan W.
<x xml:space="preserve">Abstract</x> DNA Labeling: U. Rieder and N. W. Luedtke report the incorporation of 5‐vinyl‐2′‐deoxyuridine (VdU) into cellular DNA in their Communication on page 9168 ff. The VdU can then be visualized through Diels–Alder reactions with fluorescent tetrazines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>